Inspiring heritage and symbols of local identity in contemporary Omani Graphic Art (Al-Academy, 2021)
The research aims to monitor and analyze the visual and symbolic features, derived from the Omani heritage, and inspired by the concept of local identity, for a selection of contemporary Omani graphic art works, which represent a mixed, multi-category of research sample, comprising three levels: the works of professional Omani artists, and the works of young artists and specialized students, as well as the work of a number of active academics in the field of graphic theorizing and teaching. The sample is also divided - in terms of technical classification - into a category of works executed using traditional engraving and printing media, and a category of works executed using modern and digital graphic printing media.Through the data and results resulting from this analysis, the research deals with the extrapolation of the Omani graphic art trajectories, with its distinctive visual identity, in the context of the three previously mentioned categories